2010
DOI: 10.1161/strokeaha.110.594432
|View full text |Cite
|
Sign up to set email alerts
|

Maps of Time to Maximum and Time to Peak for Mismatch Definition in Clinical Stroke Studies Validated With Positron Emission Tomography

Abstract: Background and Purpose-Perfusion-weighted imaging-derived maps of time-to-maximum (Tmax) are increasingly used to identify the tissue at risk in clinical stroke studies (eg, DEFUSE and EPITHET). Using quantitative positron emission tomography (PET), we evaluated Tmax to define the penumbral flow threshold in stroke patients and compared its performance to nondeconvolved time-to-peak (TTP) maps. Methods-Comparative perfusion-weighted imaging and quantitative 15O-water PET images of acute stroke patients were an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
121
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 135 publications
(134 citation statements)
references
References 21 publications
12
121
0
1
Order By: Relevance
“…Similarly, in EPITHET (Echoplanar Imaging Thrombolytic Evaluation Trial), both the size and the severity of PWI lesions correlated with clinical outcomes (Parsons et al, 2010). Recent data have suggested a B90% sensitivity and specificity for Tmax > 5.5 seconds to identify the PET-defined penumbra rCBF threshold of 20 mL/100 g per min (Zaro-Weber et al, 2010). These results suggest that quantification of the severity of PWI lesions can improve accuracy for identification of tissue that is in the penumbra.…”
Section: Advances In Perfusion-weighted Imaging Techniquesmentioning
confidence: 86%
See 1 more Smart Citation
“…Similarly, in EPITHET (Echoplanar Imaging Thrombolytic Evaluation Trial), both the size and the severity of PWI lesions correlated with clinical outcomes (Parsons et al, 2010). Recent data have suggested a B90% sensitivity and specificity for Tmax > 5.5 seconds to identify the PET-defined penumbra rCBF threshold of 20 mL/100 g per min (Zaro-Weber et al, 2010). These results suggest that quantification of the severity of PWI lesions can improve accuracy for identification of tissue that is in the penumbra.…”
Section: Advances In Perfusion-weighted Imaging Techniquesmentioning
confidence: 86%
“…More advanced PWI techniques, including deconvolution sequences that account for differences in arterial input to vessels with normal flow, appear to produce more accurate estimates of the regions of hypoperfusion that define the outer boundaries of the penumbra. Although PWI provides a number of parameters including mean transit time and cerebral blood volume, recently there has been focus on the maximum of the tissue residue function (Tmax) obtained by deconvolution (Zaro-Weber et al, 2010). Although the physiologic interpretation of Tmax is complex, it reflects the degree of lag between the arterial input and the tissue response, as well as dispersion and mean transit time (Calamante et al, 2010).…”
Section: Advances In Perfusion-weighted Imaging Techniquesmentioning
confidence: 99%
“…So far, only 1 study has been conducted comparing direct TTP and deconvolution-based Tmax estimation. 13 With PET as a criterion standard, it was concluded that deconvoluted Tmax does not perform significantly better than the direct TTP estimation. Moreover, the optimal TTP delay threshold was estimated at 4.2 seconds, while the optimal Tmax threshold was determined at 5.5 seconds in this study.…”
Section: Discussionmentioning
confidence: 99%
“…However, the findings of these studies are ambiguous, with identified optimal delay thresholds ranging from 4 to 6 seconds, depending on the applied methods and validations. 4,12,13 Several factors may influence the PWI analysis, such as the use and localization of the arterial input function. 14,15 Apart from this, there is another important aspect of PWI analysis that has not attracted much attention; that is the method for computation of TTP or Tmax parameter maps.…”
mentioning
confidence: 99%
“…However, subsequent research has demonstrated that much of the Tmax2-6 seconds region is 'benign oligemia'-unlikely to infarct even in the absence of reperfusion. [12][13][14] Hence Tmax46 seconds is now the preferred perfusion threshold, and we therefore also examined the mean Tmax within the Tmax46 seconds region and a modified ratio of Tmax 414 seconds to Tmax46 seconds to provide a similar index to the original 'hypoperfusion intensity ratio'.…”
Section: Perfusion Processingmentioning
confidence: 99%